Consequences of rising income inequality: a comment - Horst Siebert (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
Rising income inequality is an anglo Saxon problem. For most of the other OECD countries, earnings dispersion is rather persistent. Vertical mobility is to be taken into account. The paper also looks at the relationship of income inequality, growth and employment. It elaborates the point that equity orientation affects the incentive system of an economy and can lead to higher unemployment.
Keywords: D3; D6; I3; J00; 330; Einkommensverteilung; Wirtschaftswachstum; Arbeitslosigkeit; Sozialstaat; Ökonomischer Anreiz; Welt; Theorie